Pengaruh Ekuitas Merek Terhadap Preferensi Merek dan Niat Beli Konsumen Pada Produk iPhone di Kota Denpasar - Prabhawedasattya, I Gusti Ayu Putri Anggrihita; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen, 2013)
The main objective of this study was to determine the effect of brand equity on brand preference and purchase intention of consumers. This study examines three variables: brand equity, brand preference, and purchase intention of consumers conducted by the opinion of a teenager who uses an iPhone and live in Denpasar total of 120 respondents. Equation models and hypothesis in this study were tested using Structural Equation Modelling analysis tools (SEM). The results of this study indicate that brand equity is positive and significant effect on brand preference and purchase intention of consumers. Keywords : brand equity, brand preference, purchase intention, smartphone